2010
DOI: 10.1007/s00213-009-1751-9
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor stimulant effects of acute and repeated intrategmental injections of salsolinol in rats: role of μ-opioid receptors

Abstract: Salsolinol induces locomotor activity and motor sensitization after intra-VTA administration. Moreover, the implication of the mu-opioid receptors was shown since the treatment with naltrexone or beta-FNA was able to suppress the salsolinol effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 49 publications
10
38
0
Order By: Relevance
“…Thus, clear physiological effects are observed when only one side is injected. In line with this view, in a previous study (Quintanilla et al 2014), we injected unilaterally the same dose of (RS)-SAL (30 pmol) that (Hipólito et al 2010(Hipólito et al , 2011 had injected bilaterally, obtaining the same results on locomotor activity and CPP.…”
Section: Drug Microinjection Proceduressupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, clear physiological effects are observed when only one side is injected. In line with this view, in a previous study (Quintanilla et al 2014), we injected unilaterally the same dose of (RS)-SAL (30 pmol) that (Hipólito et al 2010(Hipólito et al , 2011 had injected bilaterally, obtaining the same results on locomotor activity and CPP.…”
Section: Drug Microinjection Proceduressupporting
confidence: 78%
“…Ammonium acetate was from Merck (Darmstadt, Germany) and triethylamine was from Sigma (St. Louis, MO, USA). For intracerebral administration, SAL was diluted with artificial cerebrospinal fluid (aCSF, containing 120.0 mM NaCl, 4.8 mM KCl, 1.2 mM KH2PO4, 1.2 mM MgSO4, 25.0 mM NaHCO3, 1.2 mM CaCl2, 10 mM d-glucose and 0.2 mM ascorbate, pH 6.5) for slow injection (1.0 μl) into the VTA (30 pmol/μl), according to Hipólito et al (2010Hipólito et al ( , 2011.…”
Section: Drugs and Solutionsmentioning
confidence: 99%
“…Behavioral and neurochemical studies have shown that acetaldehyde and salsolinol have stimulating properties into the pVTA (Rodd-Henricks et al, 2002;Rodd et al, 2008;Sanchez-Catalan et al, 2009;Hipolito et al, 2010Hipolito et al, , 2011. Accordingly, it has been observed that they enhance the activity of the pVTA dopamine neurons (Melis et al, 2007;.…”
Section: Electrophysiologicalmentioning
confidence: 97%
“…Additionally, SAL has been shown to possess a high affinity for the μ (MOR) opioid receptor (Airaksinen et al, 1984). SAL-induced locomotor activity, conditioned place preference, and stimulated DA release in the AcbSh can be reduced by microinjections of MOR antagonists into the posterior VTA (Hipolito et al, 2010(Hipolito et al, , 2011.…”
Section: Alcohol Acetaldehyde and Acetaldehyde Productsmentioning
confidence: 99%
“…Thus, the reinforcing actions of all 3 compounds in the posterior VTA is dependent upon VTA DA neuronal activity, since quinpirole would act to stimulate D 2 autoreceptors (reduction in DA activity). SAL microinjected into the VTA will produce a conditioned place preference (Hipolito et al, 2010(Hipolito et al, , 2011. Reverse microdialysis of SAL has been shown to modulate DA levels within the Acb (Hipolito et al, 2009).…”
Section: Behavioral Pharmacology Of Acetaldehyde Within the Mesolimbimentioning
confidence: 99%